The quality is in the eye of the beholder: The perspective of FTIR and UV resonant Raman spectroscopies on extracted nucleic acids. (30th January 2018) - Zucchiatti, P.; Latella, K.; Birarda, G.; Vaccari, L.; Rossi, B.; Gessini, A.; Masciovecchio, C.; D'Amico, F.
Abstract: The quality of a sample has always to be considered with respect to its purposes and to the technique used for assessing it. The aim of this work is to point out the most common interfering agents that vibrational spectroscopists may find when analyzing nucleic acids extracted from cellular cultures. Fourier transformed infrared and ultraviolet‐resonant Raman measurements have been carried out on DNA and RNA samples extracted from B16 cell cultures by standard protocols used in molecular biology. The routinely adopted quality control procedure, based on ultraviolet spectrophotometry absorption measurements, could only indicate the absence of protein, phenol, or other contaminants that absorb strongly at or near 280 nm. However, DNA and RNA samples of good quality from a biological perspective clearly showed the presence of chemicals interfering with the vibrational measurements, mainly ethanol and guanidinium salts. Here, we propose fast and inexpensive strategies for tailoring the extraction protocols in light of the requirements of both vibrational spectroscopies that allowed obtaining nucleic acid samples with ethanol concentration below the detection limit of both techniques and with a significantly reduced spectral interference from guanidinium salts. Abstract : The aim of this study is to point out the most common interfering agents that vibrational spectroscopists may find when analyzing extracted nucleic acids. Fourier transform infrared and ultraviolet‐resonant Raman measurements have been carried out on DNA and RNA samples of B16 cells, extracted by tailoring standard protocols used in molecular biology to vibrational spectroscopy. By adopting simple, rapid, and inexpensive precautions, we could obtain reliable and informative vibrational spectra also for noncommercial nucleic acids.